‘Basic Color Categories’ in the Language-Game Perspective - Beran, Ondřej (Organon F, 2012)
In this paper I will discuss some interesting philosophical questions bound to color science, in its variant founded by Berlin and Kay’s linguistic and anthropological research. I will first refer to various criticisms, expressed by dissenting scientists. Further criticisms implied by a rather philosophical perspective will follow; a particular attention is paid to the question of synchronicity vs . diachronicity. The controversy about Berlin and Kay’s conception is paralleled by the development of Wittgenstein’s views on color that I will sketch in short. Wittgenstein’s philosophy offers tools for illuminating the problem from yet another point of view. In the final part of the paper, I will try to point to the limits of the conception of basic color categories, but also to assess its relevance and possible philosophical contribution in terms of language games variety; especially with respect to the Color Incompatibility The orem and its implications.